2012
DOI: 10.1007/s11920-012-0309-4
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder Genomics: Update for Clinicians

Abstract: Attention deficit, hyperactivity disorder (ADHD) is familial and highly heritable. Several candidate genes involved in neurotransmission have been identified, however these confer minimal risk, suggesting that for the most part, ADHD is not caused by single common genetic variants. Advances in genotyping enabling investigation at the level of the genome have led to the discovery of rare structural variants suggesting that ADHD is a genomic disorder, with potentially thousands of variants, and common neuronal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 125 publications
1
21
0
6
Order By: Relevance
“…Genetic studies indicate that ADHD is highly heritable but is a polygenetic disorder with thousands of genes likely implicated, all with small effect size (Elia et al, 2012;Akutagava-Martins et al, 2013). Candidate gene studies have shown a small linkage with the DArelated genes DR5 and the DA transporter DAT1, as well as the catecholamine-related genes DRD4 and catechol-O-methyltransferase and the NE-related genes DBH and ADRA2A (Caylak, 2012).…”
Section: Relevance To Human Disordersmentioning
confidence: 99%
“…Genetic studies indicate that ADHD is highly heritable but is a polygenetic disorder with thousands of genes likely implicated, all with small effect size (Elia et al, 2012;Akutagava-Martins et al, 2013). Candidate gene studies have shown a small linkage with the DArelated genes DR5 and the DA transporter DAT1, as well as the catecholamine-related genes DRD4 and catechol-O-methyltransferase and the NE-related genes DBH and ADRA2A (Caylak, 2012).…”
Section: Relevance To Human Disordersmentioning
confidence: 99%
“…Als Erwachsene zeigten beispielsweise 20% der als Kinder mit ADHS diagnostizierten Patienten persistierende Symptome, 20% eine stabile Verbesserung und 60% mittelmäßige Verbesserungen in der emotionalen, schulisch/beruflichen und sozialen Anpassung [Spencer et al, 2007]. Diese Befunde bestätigend konnten Lahey und Willcutt [2010] Elia et al, 2012]. Daraus folgt zweierlei: Zum einen müssen solche moderierenden und mediierenden Faktoren in der Entwicklungsforschung der ADHS berücksichtigt werden; zum anderen muss die jeweils entwicklungstypische Symptomatik sehr genau beschrieben werden, damit Entwicklungstypen korrekt identifiziert werden können.…”
Section: Adhs Als Entwicklungsstörungunclassified
“…Zur besseren Differenzierung von genetischen und umweltbedingten Einflussfaktoren auf die Ätiologie der ADHS ist man jedoch auf Zwillingsund Adoptionsstudien angewiesen. Eine Analyse von 20 durchgeführten Zwillingsstudien ergab eine Heritabilitätsschätzung von 76 % [124], wobei die Heritabilitätsschätzer mit zunehmendem Alter geringer ausfallen [125]. Außerdem ermittelten Studien für eineiige Zwillinge deutlich höhere Konkordanzraten als für zweieiige Zwillinge, was die Bedeutung genetischer Einflüsse zusätz-lich unterstreicht [126].…”
Section: Molekulargenetische Untersuchungenunclassified
“…[143]) verweisen aufgrund der mäßigen OR darauf, dass selbst bedeutsame Genvarianten keinen prädiktiven Wert für die Erkrankung haben. Wenn überhaupt, scheinen einzelne Gene jeweils nur einen schwachen Effekt zu besitzen [125].…”
Section: Molekulargenetische Untersuchungenunclassified